2014
DOI: 10.3109/01443615.2014.948408
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between inflammatory markers and insulin resistance in pregnancy

Abstract: Gestational diabetes mellitus (GDM) is associated with an increased risk of postpartum type 2 diabetes mellitus and cardiovascular risk factors, such as obesity, hypertension, dyslipidaemia and systemic inflammation. We aimed to evaluate further lipid profile and inflammatory status assessed by high sensitive C-reactive protein (hsCRP) and TNF-α in GDM. Based on oral glucose tolerance testing, participants were stratified into three groups: normal 50 g glucose challenge test (GCT), normal 100 g glucose toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
(16 reference statements)
1
26
0
Order By: Relevance
“…Our results are consistent with Retnakaran et al who demonstrated obesity during pregnancy elicits an inflammatory response with possible downstream metabolic sequelae including insulin resistance [41]. Similarly, Korkmazer et al found higher inflammation among insulin resistant pregnant women with and without a classification of gestational diabetes [42]. The clinical implications of this could be substantial as the combination of obesity and insulin resistance during pregnancy can lead to gestational diabetes [13].…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with Retnakaran et al who demonstrated obesity during pregnancy elicits an inflammatory response with possible downstream metabolic sequelae including insulin resistance [41]. Similarly, Korkmazer et al found higher inflammation among insulin resistant pregnant women with and without a classification of gestational diabetes [42]. The clinical implications of this could be substantial as the combination of obesity and insulin resistance during pregnancy can lead to gestational diabetes [13].…”
Section: Discussionsupporting
confidence: 90%
“…Maternal peripheral insulin resistance, low grade inflammation, and oxidative stress are central features of GDM . A key strength of this study is the combined use of in vitro and in vivo models to investigate the ability of naringenin to disrupt pathways known to GDM pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is a central feature of GDM. There is extensive evidence to suggest that low‐grade maternal inflammation contributes to the peripheral insulin resistance characteristic of GDM . Several studies have demonstrated that pro‐inflammatory mediators, such as TNF, and pathogenic factors, such as bacterial and viral products, can induce defects within the insulin signaling pathway in skeletal muscle .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking these results together, higher level of CG decreased the expression of insulin-responsive genes and reduced insulin-stimulated glucose uptake in 3T3-L1 adipocytes, which indicated that CG may impair insulin sensitivity in vivo to induce the development of GDM, in view of higher CG in pregnancy and GDM. Inflammation in pregnancy is correlated with IR in GDM (Wolf et al 2004, Korkmazer & Solak 2014. As inflammatory cytokines, such as TNF-a (Hotamisligil et al 1993), IL6 (Rotter et al 2003) and PAI1 (Shimomura et al 1996) and chemokines such as MCP1 (Sartipy & Loskutoff 2003, Kanda et al 2006 are expressed in adipose tissue, we further assessed changes in cytokine expression after incubation 3T3-L1 adipocytes with CG.…”
Section: Discussionmentioning
confidence: 99%